Factors associated with perceived stigma among people living with HIV/AIDS in post-conflict northern Uganda. - Nattabi, Barbara; Li, Jianghong; Thompson, Sandra C; Orach, Christopher G; Earnest, Jaya (AIDS education and prevention : official publication of the International Society for AIDS Education, 2011)
HIV-related stigma continues to persist in several African countries including Uganda. This study quantified the burden of stigma and examined factors associated with stigma among 476 people living with HIV (PLHTV) in Gulu, northern Uganda. Data were collected between February and May 2009 using the HIV/AIDS Stigma Instrument-PLWA. Females more than males, respondents aged above 30 years, and those who had been on antiretroviral therapy for a longer time experienced higher levels of stigma. Verbal abuse and negative self-perception were more common forms of stigma. The association between antiretroviral therapy and stigma suggested that organizational aspects of antiretroviral delivery may lead to stigmatization of PLHIV. Interventions such as counseling of PLHIV, education of health workers and the community would lead to reductions in negative self-perception and verbal abuse and in turn improve the quality of life for PLHIV in northern Uganda.
Keywords: Adolescent; Adult; Antiretroviral Therapy, Highly Active; Cross-Sectional Studies; Female; HIV Infections; Humans; Male; Middle Aged; Prejudice; Questionnaires; Self Concept; Social Isolation; Socioeconomic Factors; Stereotyping; Uganda; War; Young Adult